PENGARUH BODY SHAMING TERHADAP PERILAKU SOSIAL SISWA SMP PUJA HANDAYANI PALEMBANG - Taty Fauzy; Sindi Lestari Putri (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2021)
Bullying or bullying ranks fourth in cases of violence in education in Indonesia. One form of bullying is body shaming. The impact of body shaming on students' social behavior is withdrawing from the social environment to cause a person to become depressed. This study aims to determine the actions of body shaming on the social behavior of students at Puja Handayani Junior High School Palembang. Descriptive quantitative research method with data analysis using regression with data processing using statistical assistance (SPSS version 20). The total population is 93 students. The sample was determined based on the results of the pretest that 50 students in filling out the questionnaire experienced body shaming at school. The results of the post test showed that the body shaming category experienced by students was at a high level, namely 32% (16 people), 60% (30 people) experienced body shaming in the medium category and 8% (4 people) experienced body shaming in the low category. This study uses a significance of 0.010 (0.05). Based on field data, more than half of the student population experienced bullying at school. Based on (R Square obtained = 0.215) body shaming contributes to changes in students' social behavior, meaning that the contribution of the body shaming variable is 21.5% causing disruption of student behavior in socializing at school, the rest is influenced by factors outside this variable.